A debate on the top-down approach to architectural interventions in conflicted historic cities: Jerusalem's Museum of tolerance - Başarır, Hacer; Yara, Sahifi; Önal Hoşkara, Şebnem (Locke Science Publ Co Inc, 117 West Harrison Bldg Suite 640-L221, Chicago, Il 60605 USA, 2016)
The focus of this paper is the extravagant architectural works designed and built in conflicted historic cities, where continuity with the physical environment and social and political realities is critical. The paper will discuss the decision-making process at both the planning and urban design level and the architectural-design level. For this purpose, the paper will critically evaluate an attempt to intervene architecturally in the conflict zone of the historic walled city of Jerusalem, focusing on Frank Gehry's design proposal for the Museum of Tolerance Jerusalem (MOTJ) and the contradictory symbolic meanings this kind of architecture creates in relation to conflict. The MOTJ project, which has followed a top-down decision-making process since its conception and whose goal is to contribute to peace in Jerusalem, is a helpful example for understanding the relationship between the trilogy of conflict, historic cities, and architectural intervention. The paper concludes that architectural interventions can successfully contribute to conflicted historic sites figuratively and literally only if they are truthful to the empirical reality of the context and based on real and common grounds recognized by all parties involved throughout the process.
Keywords: Walled City; North Cyprus; Erasure